(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
Artificial Intelligence (AI) is reshaping the landscape of language education, transforming how teachers design lessons and how learners practice speaking, listening, reading, and writing. This article explores the role of AI in the future of language classrooms, focusing on trends such as personalized learning paths, real-time feedback, virtual interlocutors, and data-driven instruction. It also examines emerging concerns, including algorithmic bias, privacy, dependence on technology, and the risk of marginalizing low-resource languages. Drawing on recent research, the article argues that the most promising future is one of “human-centered AI,” where technology supports teachers and deepens rather than replaces authentic human interaction in language learning.